Clinical utility of pharmacogenomics in the management of hepatitis C - Trinks, Julieta (2014)
Hepatitis C virus (HCV) was identified for the first time more than 20 years ago. Since then, several studies have highlighted the complicated aspects of this viral infection in relation to its worldwide prevalence, its clinical presentation, and its therapeutic response. Recently, two landmark scientific breakthroughs have moved us closer to the successful eradication of chronic HCV infection. First, response rates in treatment-naïve patients and in prior non-responders to pegylated-interferon-α and ribavirin therapy are increasing as a direct consequence of the development of direct-acting antiviral drugs. Secondly, the discovery of single-nucleotide polymorphisms near the interleukin 28B gene significantly related to spontaneous and treatment-induced HCV clearance represents a milestone in the HCV therapeutic landscape. The implementation of this pharmacogenomics finding as a routine test for HCV-infected patients has enhanced our understanding of viral pathogenesis, has encouraged the design of ground-breaking antiviral treatment regimens, and has become useful for pretreatment decision making. Nowadays, interleukin 28B genotyping is considered to be a key diagnostic tool for the management of HCV-infected patients and will maintain its significance for new combination treatment schemes using direct-acting antiviral agents and even in interferon-free regimens. Such pharmacogenomics insights represent a challenge to clinicians, researchers, and health administrators to transform this information into knowledge with the aim of elaborating safer and more effective therapeutic strategies specifically designed for each patient. In conclusion, the individualization of treatment regimens for patients with hepatitis C, that may lead to a universal cure in future years, is becoming a reality due to recent developments in biomarker and genomic medicine. In light of these advances, we review the scientific evidence and clinical implications of recent findings related to host genetic factors in the management of HCV infection.